Straightening History - Kar Yen Leong (Journal of Southeast Asian Human Rights, 2021)
In the aftermath of the attempted 1965 coup, many dissidents, leftists, and suspected Communists were either ‘eradicated’ or incarcerated in prisons all over Indonesia. Since their release, these political prisoners continue to face state-enforced discrimination and stigmatisation. The marginalization of ex-political prisoners by both the state and local communities has continued through Indonesia’s democratic transition following President Suharto’s downfall in 1998. This is compounded by the presence of right-wing groups who continue to harass them, labelling them as neo-Communists inimical to the Indonesian body politic. Through direct engagement with former political prisoners, I aim to understand rehabilitative efforts through support groups. In preliminary interviews, many eks-tapol refer to the need to ‘straighten’ history. This discourse highlights their need to be recognized as ‘whole’ citizens of Indonesia. I explore the state’s struggle to address this dark chapter in Indonesian history, what it means to ‘straighten’ history and how eks-tapol engage with support groups to re-define their position within the community, denoting a strengthened sense of dignity and humanity. It is hoped that this research will contribute to efforts to understand and protect the rights of eks-tapol and other victims of political persecution in Southeast Asia.